EXPERIMENTAL VALIDATION OF CUMULATIVE SURFACE LOCATION ERROR FOR TURNING PROCESSES - Adam K. Kiss; Daniel Bachrathy (Acta Polytechnica CTU Proceedings)
The aim of this study is to create a mechanical model which is suitable to investigate the surface quality in turning processes, based on the Cumulative Surface Location Error (CSLE), which describes the series of the consecutive Surface Location Errors (SLE) in roughing operations. In the established model, the investigated CSLE depends on the currently and the previously resulted SLE by means of the variation of the width of cut. The phenomenon of the system can be described as an implicit discrete map. The stationary Surface Location Error and its bifurcations were analysed and flip-type bifurcation was observed for CSLE. Experimental verification of the theoretical results was carried out.